Pengaruh Temuan Sistem Pengendalian Internal, Temuan Kepatuhan Peraturan Perundangan, Tindak Lanjut Hasil Pemeriksaan dan Penyelesaian Kerugian Daerah Terhadap Opini Audit Atas Laporan Keuangan Pemerintah Daerah Kota di Pulau Sumatera - Muhammad Ramadhan Alendra; Henny Yulsiati; Anggeraini Oktarida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study was conducted with the aim of analyzing the impact of “internal control system findings, compliance with laws and regulations findings, follow-up of examination results, and settlement of regional losses on the audit opinion of the financial statements of municipal governments located on the island of Sumatra”. This study employs a quantitative methodology, utilising secondary data sourced from the official website www.bpk.go.id. The research encompassed 33 cities on the island of Sumatra, comprising a total sample size of 150 individuals. This research employed a purposive sampling technique for sample determination. The hypothesis testing procedure is conducted via logistic regression analysis using Eviews 12 software. The findings indicated that, individually, Internal Control System Findings exert a positive and significant influence on Audit Opinions. The findings regarding adherence to laws and regulations, the follow-up on examination results, and the resolution of regional losses do not significantly impact the audit opinion. Simultaneous testing shows that the variables of Internal Control System Findings, Regulatory Compliance Findings, Follow-Up of Audit Results, and Regional Loss Settlement collectively have a significant influence on the Audit Opinion of the LKPD of the City on the Island of Sumatra.